Duodenal leaks after pancreas transplantation with enteric drainage – characteristics and risk factors. (23rd February 2015) - Spetzler, Vinzent N.; Goldaracena, Nicolas; Marquez, Max A.; Singh, Sunita K.; Norgate, Andrea; McGilvray, Ian D.; Schiff, Jeffrey; Greig, Paul D.; Cattral, Mark S.; Selzner, Markus
Summary Pancreas–kidney transplantation with enteric drainage has become a standard treatment in diabetic patients with renal failure. Leaks of the graft duodenum (DL) remain a significant complication after transplantation. We studied incidence and predisposing factors of DLs in both simultaneous pancreas–kidney (SPK) and pancreas after kidney (PAK) transplantation. Between January 2002 and April 2013, 284 pancreas transplantations were performed including 191 SPK (67.3%) and 93 PAK (32.7%). Patient data were analyzed for occurrence of DLs, risk factors, leak etiology, and graft survival. Of 18 DLs (incidence 6.3%), 12 (67%) occurred within the first 100 days after transplantation. Six grafts (33%) were rescued by duodenal segment resection. Risk factors for a DL were PAK transplantation sequence (odds ratio 3.526, P = 0.008) and preoperative immunosuppression (odds ratio 3.328, P = 0.012). In the SPK subgroup, postoperative peak amylase as marker of preservation/reperfusion injury and recipient pretransplantation cardiovascular interventions as marker of atherosclerosis severity were associated with an increased incidence of DLs. CMV‐mismatch constellations showed an increased incidence in the SPK subgroup, however without significance probability. Long‐term immunosuppression in PAK transplantation is a major risk factor for DLs. Early surgical revision offers the chance of graft rescue.